Handbook of applied behavior analysis - Fisher, W.W.; Piazza, C.C.; Roane, H.S. (New York : The Guilford Press, 2011)
Describing the state of the science of applied behavior analysis (ABA), this comprehensive handbook provides detailed information about theory, research, and intervention. The contributors are leading ABA authorities who present best practices in behavioral assessment and demonstrate evidence-based strategies for supporting positive behaviors and reducing problem behaviors. Conceptual, empirical, and procedural building blocks of ABA are reviewed and specific applications described in education, autism treatment, safety skills for children, and other areas. The volume also addresses crucial professional and ethical issues, making it a complete reference and training tool for ABA practitioners and students.
Includes index.
Keywords: Classroom management; Classroom management -- Case studies; Organizational behavior